Employment decisions: The case of Peruvian rural youth - Boyd, Chris (2014)
This paper identifies the determinants of employment for rural young people aged 15 to 29 from the National Survey of Youth (Enajuv 2011), the first such survey representative of Peruvian rural youth. Data from this survey shows that rural unemployment is half of the urban rate, and that participation rates in labor markets are higher for rural youth. The pattern is different for rural young women, only 62.1% of whom provide labor to the market. The results, from a logit model, show that the decision to enter the labor market is closely linked to the decision to study and to undertaking unpaid family work. Moreover, the high percentages of youth engaged in unpaid family work (39% for men, 42% women) seem to show that the decision to participate in the labor market is made at the household level and not individually.